Automatic Music Summarization. A “Thumbnail” Approach - GŁACZYNSKI, Jakub; ŁUKASIK, Ewa (Archives of Acoustics, 2011)
In the paper, various approaches to automatic music audio summarization arediscussed. The project described in detail, is the realization of a method for extractinga music thumbnail – a fragment of continuous music of a given duration timethat is most similar to the entire music piece. The results of subjective assessmentof the thumbnail choice are presented, where four parameters have been taken intoaccount: clarity (representation of the essence of the piece of music), conciseness(the motifs are not repeated in the summary), coherence of music structure, andoverall quality of summary usefulness.